The best of O. Henry. - Henry, O., 1862-1910. (Philadelphia : Running Press, 1978)
A collection of twenty-six short stories, all but one of which originally appeared in the "New York World"
Keywords: Short stories; New York (N.Y.) -- Social life and customs -- Fiction